LSPR‐Induced Catalysis: LSPR‐Induced Catalytic Enhancement Using Bimetallic Copper Fabrics Prepared by Galvanic Replacement Reactions (Adv. Mater. Interfaces 16/2019). Issue 16 (23rd August 2019) - Anderson, Samuel R.; O'Mullane, Anthony P.; Della Gaspera, Enrico; Ramanathan, Rajesh; Bansal, Vipul
Abstract : In article number1900516, Rajesh Ramanathan, Vipul Bansal, and co‐workers show the use of galvanic replacement reactions to create LSPR‐active bimetallic fabrics of copper‐gold and copper‐silver. The atomic scale inclusion of noble metals within copper fabrics significantly enhances their catalytic efficiency under visible light photoexcitation due to the synergistic LSPR‐activity of the bimetallic fabrics. The minute amounts of noble metals also improve the stability of intrinsically‐efficient copper catalysts, allowing catalyst recyclability. The cover image was designed by Ella Maru Studio.